5-Hydroxy-7-methoxy-2-methyl-4H-chromen-4-one from Dysoxylum macrocarpum (Meliaceae) - Najmuldeen, I.A.; Hadi, A.H.A.; Awang, K.; Mohamad, K.; Ng, S.W. (International Union of Crystallography, 2010)
Both independent molecules in the asymmetric unit of the title compound, C(11)H(10)O(4), are almost planar (r.m.s. deviations = 0.011 and 0.033 A). In both molecules, the hydroxy group is intramolecularly hydrogen bonded to the ketonic O atom. The independent molecules are stacked alternately along the a axis, with the centroids of their chromene ring separated by distances of 4.490 (1) and 3.621 (1) A.